2023
DOI: 10.1101/2023.02.02.526661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noradrenaline release from the locus coeruleus shapes stress-induced hippocampal gene expression

Abstract: Exposure to an acute stressor triggers a complex cascade of neurochemical events in the brain. However, deciphering their individual impact on stress-induced molecular changes remains a major challenge. Here we combine RNA-sequencing with selective pharmacological, chemogenetic and optogenetic manipulations to isolate the contribution of the locus coeruleus - noradrenaline (LN-NA) system to the acute stress response. We reveal that NA-release during stress exposure regulates a large and reproducible set of gen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 88 publications
4
4
0
Order By: Relevance
“…For example, yohimbine strongly suppresses clusters 1 and 11, which capture the initiation and termination of a supported rear, respectively (see Suppl. Video 10 and 11), in line with our previous findings that yohimbine reduces supported rearing 24 .…”
Section: Behavioral Flow Analysis (Bfa)supporting
confidence: 90%
See 2 more Smart Citations
“…For example, yohimbine strongly suppresses clusters 1 and 11, which capture the initiation and termination of a supported rear, respectively (see Suppl. Video 10 and 11), in line with our previous findings that yohimbine reduces supported rearing 24 .…”
Section: Behavioral Flow Analysis (Bfa)supporting
confidence: 90%
“…We demonstrate that -within the same experimental setup -this approach can resolve behavioral phenotypes and visualize large-scale comparisons of individual animals across experimental conditions. This revealed not only a clear dissociation between acute and chronic stressors, but it identified similarities between behavioral changes induced by acute stress and noradrenergic manipulations, in line with the known biological link between acute stress and activation of the noradrenergic system through the locus coeruleus 24,55,56 . Going forward, there is likely a trade-off between identifying the optimal number of clusters to maximally boost statistical power for each given experiment, and the decision to stabilize a "reasonable" number of clusters to allow direct comparisons across large numbers of datasets collected within a given laboratory or potentially across larger research consortia.…”
Section: Limitations and Outlooksupporting
confidence: 64%
See 1 more Smart Citation
“…In the context of rearing related to spatial sampling of the environment and updating spatial information [30][31][32] , it has been found to correlate with the activity of hippocampal neurons 33 . Rearing has been shown to be reduced by acute stressors 26 , which are known to increase hippocampal activity 34,35 and recent work has shown that optogenetic activation of the locus coeruleus (LC) suppresses rearing 36 , in agreement with past observations that rearing is sensitive to the overall level of arousal 26,37 . MNs rapidly turn on and off during exploration 12,13,22 , are inhibited by noradrenaline 38 , and the LH is a site of LC innervation 39 .…”
Section: Introductionsupporting
confidence: 77%
“…(Figure 2A). Second, we added a pharmacological stress model that allowed us to introduce a graded stress response by injecting mice with variable doses of yohimbine, an α2-adrenergic receptor antagonist, which triggers strong noradrenaline release by disinhibiting the locus coeruleus 23,24 . Control animals were injected with saline (n=5), while each mouse in the treatment group received one injection of yohimbine ranging from 0.4 to 6 mg/kg (n=15; Figure 2B).…”
Section: Cluster Stabilization Enables Direct Comparisons Across Expe...mentioning
confidence: 99%